Influência do período de gestação e do tamanho da ninhada no crescimento ponderal intra-uterino de coelhos - Cury, P. R.; Nunes, JRV (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1991)
Intrauterine growth of Norfolk rabbits was studied from the 20th day of gestation until the parturition (31st day). A theoretical equation was adjusted for fetuses body weight. The exponential model was tested by stepwise regression technique after linearization. Both stage of gestation (t) and number of fetuses (n) had significant effects on the growth rate. The following equation was proposed to describe the weight of the pups: W = exp. (-12,9772).n.exp. {(0,991263-0,014007.5-0,00039.n)t} (with R2 = 0,9932). The biological coherence and the interpretation of the coefficients permitted us to conclude that similar models could be used for other multiparous species. This model can also be used with or without the presence of different factors related to fetal growth.

Foi estudado o crescimento intra-uterino de coelhos Norfolk, desde o 20o dia de gestação até a parição (31o dia), com base em uma equação teórica ajustada para o peso da ninhada (W). O modelo, de forma exponencial, foi testado usando-se técnica de regressão múltipla após sua linearização. Foram evidenciados efeitos significativos de período de gestação (t) e de tamanho de ninhadas (n). Foi proposta a equação: Ŵ = exp. (-12,9772).n.exp. {(0,991264 - 0,014007.t-0,00039.n)t} (com R2 = 0,9932), para descrever o peso da ninhada. A coerência biológica e a interpretação dos coeficientes permitem sugerir que os modelos similares poderão ser usados para o crescimento intra-uterino de outras espécies multíparas com ou sem a inclusão de outros fatores que influenciam a dinâmica do crescimento.
Effects of stage of gestation and litter size on intrauterine growth in rabbits
Keywords: PRENATAL GROWTH; BIOLOGICAL COHERENCE; MULTIPAROUS SPECIES; PARTURITION